Validation of irtGPUMCD, a GPU-based Monte Carlo internal dosimetry framework for radionuclide therapy. (May 2020) - Frezza, Andrea; Joachim-Paquet, Charles; Chauvin, Maxime; Després, Philippe
Highlights: ICRP phantoms were used to validate irtGPUMCD, a GPU-based Monte Carlo code for dose calculations in internal radiotherapy. A comparison against published results in IDAC-DOSE as well as GATE simulations was performed. An exponential track length estimator was used in irtGPUMCD as a variance reduction technique. IrtGPUMCD exhibits an excellent efficiency, with execution times (order of 1 min) compatible with clinical applications. Abstract: Purpose: Monte Carlo (MC) simulations are highly desirable for dose treatment planning and evaluation in radiation oncology. This is true also in emerging nuclear medicine applications such as internal radiotherapy with radionuclides. The purpose of this study is the validation of irtGPUMCD, a GPU-based MC code for dose calculations in internal radiotherapy. Methods: The female and male phantoms of the International Commission on Radiological Protection (ICRP 110) were used as benchmarking geometries for this study focused on 177 Lu and including 99m Tc and 131 I. Dose calculations were also conducted for a real patient. For phantoms, twelve anatomical structures were considered as target/source organs. The S-values were evaluated with irtGPUMCD simulations (10 8 photons), with gamma branching ratios of ICRP 107 publication. The 177 Lu electrons S-values were calculated for source organs only, based on local deposition of dose in irtGPUMCD. The S-value relative difference between irtGPUMCD and IDAC-DOSE were evaluated for all targets/sources considered. A DVHs comparison with GATE was conducted. An exponential track length estimator was introduced in irtGPUMCD to increase computational efficiency. Results: The relative S-value differences between irtGPUMCD and IDAC-DOSE were <5% while this comparison with GATE was <1%. The DVHs dosimetric indices comparison between GATE and irtGPUMCD for the patient led to an excellent agreement (<2%). The time required for the simulation of 10 8 photons was 1.5 min for the female phantom, and one minute for the real patient (<1% uncertainty). These results are promising and let envision the use of irtGPUMCD for internal dosimetry in clinical applications.